Learning disability and oligodendrocyte myelin glycoprotein (OMGP) gene in neurofibromatosis type 1 - Terzi, Yunus Kasim; Oğuzkan-Balci, Sibel; Anlar, Banu; Erdoğan-Bakar, Emel; Ayter, Sükriye (The Turkish Journal of Pediatrics, 2011)
Neurofibromatosis type 1 (NF1) is an autosomal dominant disease where phenotypic heterogeneity is explained by the effect of modifier genes. Thirty to 65% of patients have learning disability. The oligodendrocyte myelin glycoprotein (OMGP) gene located within the neurofibromatosis type 1 (NF1) gene might affect the phenotype of learning disability because it is expressed in the brain, and OMGP gene mutations have been associated with cognitive disturbances. We analyzed the OMGP gene in NF1 patients with and without learning disability (n = 50 each) and healthy controls (n = 100). The allele distribution of OMGP62 polymorphism was not significantly different between the groups (p = 0.447). These results do not support a relationship between the OMGP gene and the learning disability phenotype observed in NF1. Other modifying genes, post-translational modifications or receptor interactions might be involved in the phenotypic variability of NF1.